Amanda and the pot of gold - Magee, Wes (England : Ladybird books, 1998)
It's Grandma's birthday and Amanda sets off with her animal friends to find the perfect present - the pot of gold from the end of the rainbow. But lurking in the shadows is the wily fox, who has heard their plan and wants the pot of gold for himself.
Location: 3B
Keywords: Story book